2022
DOI: 10.1001/jamanetworkopen.2022.8884
|View full text |Cite
|
Sign up to set email alerts
|

Association of Perinatal and Childhood Ischemic Stroke With Attention-Deficit/Hyperactivity Disorder

Abstract: Key Points Question Does the risk of attention-deficit/hyperactivity disorder (ADHD) increase after pediatric stroke, and is that risk associated with family history of ADHD, adverse motor outcomes, or comorbid epilepsy? Findings This nationwide cohort study of 1320 patients who had perinatal or childhood stroke and 13 141 matched controls found a 2-fold increased risk of ADHD after stroke. Development of adverse motor outcomes and/or epilepsy were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In a retrospective study from the Hospital for Sick Children, externalizing symptoms of aggression and defiance were reported in as many as 30% of perinatal stroke patients [40]. A Swedish cohort study analyzed 343 children with perinatal stroke and found an almost three-fold increased risk of developing attention deficit hyperactivity disorder (ADHD) [41 ▪▪ ]; this risk significantly increased with comorbid epilepsy and/or motor deficits. Another study found that children with perinatal stroke had increased prevalence of autism spectrum disorder (ASD) compared to the general population [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a retrospective study from the Hospital for Sick Children, externalizing symptoms of aggression and defiance were reported in as many as 30% of perinatal stroke patients [40]. A Swedish cohort study analyzed 343 children with perinatal stroke and found an almost three-fold increased risk of developing attention deficit hyperactivity disorder (ADHD) [41 ▪▪ ]; this risk significantly increased with comorbid epilepsy and/or motor deficits. Another study found that children with perinatal stroke had increased prevalence of autism spectrum disorder (ASD) compared to the general population [42].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests survivors of pediatric stroke are at a high risk of behavioral disorders including ADHD and ASD [41 ▪▪ ,47]. A Swedish retrospective found that pediatric AIS increased the risk of developing ASD three-fold in survivors of childhood stroke [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When deficits are identified, implementation of therapies, educational resources, and school accommodations can help optimize school function. For example, children with a history of stroke are at risk for attention-deficit/hyperactivity disorder (ADHD) [ 259 ]. ADHD can be medically managed when identified, thereby limiting the impact on a child’s daily life.…”
Section: Therapeuticsmentioning
confidence: 99%
“…53,54 Also, risk of neuropsychiatric diseases, such as attention deficit/hyperactivity disorder and autism, is increased in children with ischemic stroke. 55,56 Stroke lesion size is correlated with worse cognitive outcome through all ages 57 while variations between ages can be seen in different domains of cognitive outcome. For example, ischemic stroke in early childhood (28 days to 6 years of age) resulted in less cognitive flexibility, processing speed, and verbal learning compared to perinatal or late childhood stroke.…”
Section: Adverse Outcomesmentioning
confidence: 99%